1974
DOI: 10.1172/jci107837
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoiesis in the Grey Collic Dog STUDIES OF THE REGULATION OF ERYTHROPOIESIS

Abstract: A B S T R A C T Hematopoiesis in the grey collie dog undergoes periodic fluctuations which involve reticulocytes, granulocytes, platelets, lymphocytes, and monocytes. This syndrome is inherited in an autosomal recessive manner and can be transmitted or abolished by appropriate bone marrow transplantation experiments, thus demonstrating this to be a primary marrow defect. Investigation of humoral regulation in this setting indicates that serum erythropoietin (ESF) also undergoes cyclic fluctuation and that shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 27 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…The columns represent the mean nucleotide levels and bars are standard errors of the mean. P values for all NL vs. GC [1][2][3][4][5][6] (Fig. 4) Enzyme assays.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The columns represent the mean nucleotide levels and bars are standard errors of the mean. P values for all NL vs. GC [1][2][3][4][5][6] (Fig. 4) Enzyme assays.…”
Section: Resultsmentioning
confidence: 99%
“…The cyclic fluctuation of the neutrophil count is reproducible and is reliably associated with fluctuations in eosinophils, monocytes, lymphocytes, platelets, and reticulocytes (1)(2)(3)(4). These periodic changes are caused by alterations in marrow cell production rates rather than alterations in rates of destruction or sequestration of cells in the circulation (2,(4)(5)(6). Studies of granulocytic and erythroid precursor cells have shown fluctuations in these committed progenitor cell populations over the cycle of cell counts but have not explained the mechanism(s) causing cyclic hematopoiesis (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Marrow transplantation studies have shown that the disorder can be eliminated by total body irradiation and bone marrow transplantation from a normal dog (6), and that the blood cycling can be produced in previously normal dogs by irradiation and infusion of grey collie marrow cells (7). Therefore, alteration ofthe intrinsic regulation of the stem cell pool or pools is thought to produce this autosomal recessive disease (4,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…1 ml of a suspension that contained 2 x 105 nucleated marrow cells, 0.1 ml of fetal calf serum (Irvine Scientific, Santa Ana, Calif. and Microbiologic Associates), 0.1 ml of a stimulatory material (CSA, see below), and 0.3% agar (BactoAgar, Difco Laboratories, Detroit, Mich.) in supplemented media were placed in 35-mm plastic dishes (Falcon Labware, Div., Becton, Dickinson & Co., Oxnard, Calif.), allowed to gel at room temperature, and placed in a 37°C, 5% CO2, 100% humidity incubator (National Appliance Co., Portland, Oreg.) for [8][9][10] d. All assays were performed in triplicate. Colonies of >50 cells were counted with an inverted microscope and results expressed as colonies per plate or colonies per 2 x 105 nucleated marrow cells.…”
Section: Introductionmentioning
confidence: 99%
“…In the grey collie variant of the disease, phlebotomy has no impact on cycling of reticulocytes or neutrophils. However, erythrocyte hypertransfusion stops reticulocyte but not neutrophil cycling (18). Neutrophils and their precursors express G-CSF receptors and play an important role in clearance of the cytokine from the circulation (19).…”
Section: Introductionmentioning
confidence: 99%